Embodiment, Environment, Disability Culture: Learning to Feel Ourselves in Space - Kuppers, Petra (Disability Studies Quarterly, 2015)
In this short montage essay, I am sharing different student and teacher perspectives on a pedagogical exercise that allows us to relearn being in space. The exercise confounds conventional disability simulation exercises, imaging ourselves to be different than who we are, by substituting an experience of who we are already, perceived differently, with a more mindful attention.